Microfluidic Preparation of Janus Microparticles With Temperature and pH Triggered Degradation Properties - Feng, Zi-Yi; Liu, Tao-Tao; Sang, Zhen-Tao; Lin, Zhen-Sheng; Su, Xin; Sun, Xiao-Ting; Yang, Hua-Zhe; Wang, Ting; Guo, Shu (Frontiers in Bioengineering and Biotechnology, 2021)
Based on the phase separation phenomenon in micro-droplets, polymer-lipid Janus particles were prepared on a microfluidic flow focusing chip. Phase separation of droplets was caused by solvent volatilization and Janus morphology was formed under the action of interfacial tension. Because phase change from solid to liquid of the lipid hemisphere could be triggered by physiological temperature, the lipid hemisphere could be used for rapid release of drugs. While the polymer we selected was pH sensitive that the polymer hemisphere could degrade under acidic conditions, making it possible to release drugs in a specific pH environment, such as tumor tissues. Janus particles with different structures were obtained by changing the experimental conditions. To widen the application range of the particles, fatty alcohol- and fatty acid-based phase change materials were also employed to prepare the particles, such as 1-tetradecanol, 1-hexadecanol and lauric acid. The melting points of these substances are higher than the physiological temperature, which can be applied in fever triggered drug release or in thermotherapy. The introduction of poly(lactic-co-glycolic acid) enabled the formation of multicompartment particles with three distinct materials. With different degradation properties of each compartment, the particles generated in this work may find applications in programmed and sequential drug release triggered by multiple stimuli.